Meridian - Walker, Alice, 1944- (Harcourt, 2003)
Meridian is a poignant and powerful story of the American South in the 1960s and of one woman who risks her life for the people she loves. Meridian Hill, a courageous young activist, creates peace and understanding by dedicating herself heart and soul to her civil rights work, touching the lives of all those she meets even when her health begins to deteriorate. With the old rules of Southern society collapsing around her, Meridian fights a lonely battle to reaffirm her own humanity, and that of all her people.